Plasmons in nanoscale and atomic-scale systems - Nagao, Tadaaki; Han, Gui; Hoang, Chung-Vu; Wi, Jung-Sub; Pucci, Annemarie; Weber, Daniel; Neubrech, Frank; Silkin, Vyacheslav M; Enders, Dominik; Saito, Osamu; Rana, Masud (Science and technology of advanced materials, 2010)
Plasmons in metallic nanomaterials exhibit very strong size and shape effects, and thus have recently gained considerable attention in nanotechnology, information technology, and life science. In this review, we overview the fundamental properties of plasmons in materials with various dimensionalities and discuss the optical functional properties of localized plasmon polaritons in nanometer-scale to atomic-scale objects. First, the pioneering works on plasmons by electron energy loss spectroscopy are briefly surveyed. Then, we discuss the effects of atomistic charge dynamics on the dispersion relation of propagating plasmon modes, such as those for planar crystal surface, atomic sheets and straight atomic wires. Finally, standing-wave plasmons, or antenna resonances of plasmon polariton, of some widely used nanometer-scale structures and atomic-scale wires (the smallest possible plasmonic building blocks) are exemplified along with their applications.